Kemampuan Tempurung Kelapa Sebagai Panel Akustik Refuser (Resonator - Difuser) Dalam Menyerap dan Mengisolasi Bunyi: Susilo Indrawati, Suyatno, Lila Yuwana - Susilo Indrawati Susilo Indrawati; Suyatno Suyatno; Lila Yuwana Lila Yuwana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
Echoes in auditorium could be improved by adding absorbent materials. The consequence of this is an emerge of various sound distribution. Therefore, this article performs the combination of two functions of a material, i.e as resonator and diffuser (known as refuser